Cleaning of high sulfur Indian coal by oil agglomeration and leaching. Issue 9 (3rd May 2018) - Ken, Bhupendra Singh; Nandi, Barun Kumar
ABSTRACT: The present paper reports an attempt for cleaning of high sulfur Indian coal with two consecutive steps of oil agglomeration at ambient temperature followed by leaching at various conditions. The physico-chemical characterizations of the raw and treated coal samples were carried out by using Fourier transform infrared (FTIR), FESEM, Thermogravimetric analysis and Differential Thermal Analysis (TGA-DTA), and petrographic techniques to assess the product quality. The petrographic and FTIR spectral analyses reveal reduction in different forms of sulfur contents in coals by the use of oil agglomeration and leaching. Scanning electron microscope morphology of the treated coal samples are attributed to the occurrence of the cavitations in the coal structure.